Development Strategy of Batik SMEs in Terungwetan Village Through Human Resources and Digital Marketing: Strategi Pengembangan UMKM Batik di Desa Terungwetan Melalui Sumber Daya Manusia dan Digital Marketing - Fransisca D.N.A, Dian; Khomariyah, Nurul; Mu’amala, Khofifatul; Rahmawati, Rizka; Wulandari, Vindiah Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
The management of UMKM in the Terungwetan village has not been optimal in marketing. One of the UMKM in the Terungwetan village, namely the Batik UMKM, has not yet provided optimal income. The purpose of this study is to increase income through improving the quality of human resources in managing village UMKM through digital marketing. The method used is to provide training in the form of lectures and tutorial learning to create accounts in digital media and manage digital media. The results obtained from this activity are, suggesting that the use of digital marketing can be followed up with regular guidance so that it can be optimal in supporting marketing activities and increasing business sales and being able to manage Human Resources (HR) as well as possible.